2014
DOI: 10.1111/iji.12152
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 single nucleotide polymorphisms in juvenile systemic lupus erythematosus

Abstract: Juvenile systemic lupus erythematosus (JSLE) is a chronic, recurrent multisystem inflammatory disease, caused by a combination of environmental events and genetic risk factors. As cytokines, including interleukin-4 (IL-4), seem to have a role in the pathogenesis of JSLE, the investigation was performed to evaluate the associations of specific single nucleotide polymorphisms (SNPs) of IL-4 and IL-4RA genes in a case-control study. Fifty-nine patients with JSLE were recruited in this study as patients' group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…It seems the role of IL4 in SLE is dependent on genetic background. Some studies showed that IL4 gene polymorphisms might be involved in the etiology and susceptibility of SLE (50,51). We showed in our recent study on JSLE patients that IL-4 gene variants are associated with JSLE and might have a role in the pathophysiology of disease (50).…”
Section: Cytokine Cascade In Systemic Lupus Erythematosusmentioning
confidence: 61%
See 1 more Smart Citation
“…It seems the role of IL4 in SLE is dependent on genetic background. Some studies showed that IL4 gene polymorphisms might be involved in the etiology and susceptibility of SLE (50,51). We showed in our recent study on JSLE patients that IL-4 gene variants are associated with JSLE and might have a role in the pathophysiology of disease (50).…”
Section: Cytokine Cascade In Systemic Lupus Erythematosusmentioning
confidence: 61%
“…Some studies showed that IL4 gene polymorphisms might be involved in the etiology and susceptibility of SLE (50,51). We showed in our recent study on JSLE patients that IL-4 gene variants are associated with JSLE and might have a role in the pathophysiology of disease (50). An association between polymorphisms of interleukin-4 gene and discoid rash was reported in Chinese patients with SLE (52).…”
Section: Cytokine Cascade In Systemic Lupus Erythematosusmentioning
confidence: 67%
“…146 IL-4 is elevated in some human SLE patients 147,148 and SNPs in the IL-4 locus are associated with increased susceptibility to lupus. 149,150 In keeping with increased levels of Th2 cytokines in vivo in Ets1 −/− mice, B cells from these animals show increased isotype-switching to IgG1 and IgE and increased numbers of plasma cells ( 18,77 and unpublished data). Although it is not yet clear whether the IgG1 or IgE produced by Ets1 −/− mice is pathogenic, it is interesting to note that pathogenic IgE autoantibodies have recently been described in Lyn knockout mice that share many similar phenotypic features with Ets1 knockout mice (see above).…”
Section: Introductionmentioning
confidence: 75%
“…Nevertheless, most of the association studies have focused mainly on patients with adult-onset SLE. To the best of our knowledge, there are only a few number of genetic studies on juvenile-onset SLE [2,3,[20][21][22][23]. In this study, we have evaluated a group of Iranian patients with JSLE for the PD1.1, PD1.3 and PD1.9 SNPs.…”
Section: Discussionmentioning
confidence: 99%